Pengembangan Perangkat Pembelajaran Fisika Berbasis Moodle - Lovy Herayanti; Muhammad Fuaddunnazmi; Habibi Habibi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2017)
The purpose of this research is to develop a physics learning tools with Moodle that can be used on students in physics courses. The type of this research is Research and Development (R & D). Research and Development is a process or steps to develop a new product or refine an existing product, which can be accounted for. Broadly speaking, the R & DÃ¢â¬â¢s steps consisted of three stages, namely: preliminary study, design/model development, and model testing. The subject of this research is a student of Department of Physics Education at FPMIPA IKIP Mataram who is studying at Odd Semester Academic Year 2016/2017. Based on the validation of physics learning tools with Moodle, it obtained products that have been validated with a good categorized score and can be used for the next stage. The development of Moodle-based learning tools developed was complemented by textbooks, Moodle guides, and assessment instruments.